Behaviour of a High Frequency Parallel Quasi Resonant Inverter Fitted Induction Heater with Different Switching Frequencies - Avijit Chakraborty; Pradip Kumar Sadhu; Kallol Bhaumik; Palash Pal; Nitai Pal (International Journal of Electrical and Computer Engineering (IJECE), 2016)
This paper investigates the behavior of a high frequency parallel quasiresonantinverter fitted domestic induction heater with different switching frequencies. The power semiconductor switch Insulated Gate Bipolar Junction Transistor (IGBT) is incorporated in this high frequency inverter that can operate under ZVS and ZCS conditions during the switching operations at certain switching frequency to reduce switching losses. The proposed induction heating system responds to three different switching frequencies with providing different results. An Insulated Gate Bipolar Junction Transistor (IGBT) provides better efficiency and faster switching operations. After the complete study of the proposed induction heating system at the selected switching frequencies, the results are compared and it is decided that most reliable, efficient and effective operations from the proposed induction heater can be obtained if the switching frequency is selected slightly above the resonant frequency of the tank circuit of the resonant inverter. The proposed scheme is analyzed using Power SystemSimulator (PSIM) environment.